Psychosocial Problems among Farmers in Agricultural Areas - Dewi Novi Maharani; Nadirotul Umami; Ulfi Yuliyani; Enggal Hadi Kurniyawan; Kholid Rosyidi Muhammad Nur; Dicky Endrian Kurniawan; Alfid Tri Afandi (KHD Production, 2025)
Heavy work is one of the factors that can influence farmer stress. In addition, the high demand for labor can increase psychosocial disorders and psychological stress among farmers. This research aims to determine the management of psychosocial problems among Indonesian farmers. This research uses a literature review method which examines several academic articles related to the author's research. The data was obtained from the Google Scholar, PubMed, and Science Direct databases, and the publication years were 2020 to 2024. A systematic approach in the form of the PRISMA framework was used in selecting this literature review. In the English language literature search, the keywords